Development and evaluation of english instructional materials based on advice poetry to foster students’ moral character and language proficiency - Hasibuan, Ahmad Laut; Harahap, Nurhayati; Lubis, Nazriani; Batubara, Irpan Apandi; Wariyati, Wariyati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Improving the quality of English learning in high schools is an ongoing priority to produce graduates with strong moral character and linguistic competence. This study aimed to develop English teaching materials based on advice poetry and evaluate their effectiveness in enhancing students’ moral character and English language skills. The research employed the Research and Development (R&D) model proposed by Borg & Gall, encompassing preliminary studies, material design, and evaluation phases. The sample consisted of 120 high school students, selected through purposive sampling, who participated in the intervention. Data were analyzed using a paired t-test to measure the statistical significance of learning outcomes before and after the implementation of the developed materials. The findings indicate that the developed teaching materials align with students’ needs, adhere to curriculum standards, and meet criteria for readability, clarity, and graphical presentation. Quantitative analysis revealed a significant improvement in students' learning outcomes, with average scores increasing from 65.4 (pre-test) to 82.7 (post-test) (p < 0.001, Cohen’s d = 1.2), indicating a large effect size. Additionally, qualitative feedback showed that students were highly enthusiastic about the learning process, citing increased engagement and understanding of moral values embedded in the advice poetry. This study concludes that (1) the developed teaching materials are effective in improving both moral character and English language competence, and (2) students show positive attitudes toward poetry-based learning. The study recommends that educators incorporate advice poetry into English teaching materials to foster holistic student development. Future research could explore other literary genres or expand the sample size to generalize findings across diverse educational contexts.